Kedudukan Hukum Putusan Kedamangan Adat Dayak Terhadap Pertimbangan Hakim Dalam Putusan Perkara Pidana - Naya Putri Fadyah; Muhammad Kevin Yades; Masyita Herza Putri (UIN Sunan Kalijaga Yogyakarta, 2025)
The existence of customary law communities is recognized, as stated in Article 18B paragraph (2) and Article 28I paragraph (3) of the 1945 Constitution. This recognition indicates that the existence of customary law is still recognized in accordance with the development of society and does not violate applicable laws and regulations. According to experts, customary law communities have institutions and customary laws that regulate their behavior, including customary criminal law. One of the regions that has recognized and regulated the settlement of criminal cases through customary courts is Central Kalimantan Province, as stated in Regional Regulation 16/2008. Regarding this problem, two questions arise: (1) What is the role of kedamangan in resolving customary criminal cases? and (2) What is the position of customary decisions as a consideration for judges in deciding criminal cases. This study uses a normative legal method with a regulatory approach. The results of the study indicate that positive law and customary law applicable in society regulate the settlement of criminal cases through kedamangan, and customary decisions play an important role in judges' considerations in criminal cases in court. Masyarakat hukum adat di akui keberadaanya, sebagaimana dinyatakan dalam Pasal 18B ayat (2) dan Pasal 28I ayat (3) UUD 1945. Pengakuan ini menunjukkan bahwa keberadaan hukum adat masih diakui sepanjang sesuai dengan perkembangan masyarakat serta tidak bertentangan dengan peraturan perundang-undangan yang berlaku. Menurut para ahli, masyarakat hukum adat memiliki lembaga dan hukum adat yang mengatur perilaku mereka, termasuk hukum pidana adat. Salah satu daerah yang telah mengakui dan mengatur penyelesaian perkara pidana melalui peradilan adat adalah Provinsi Kalimantan Tengah, sebagaimana dituangkan dalam Peraturan Daerah 16/2008. Mengenai masalah ini, muncul dua pertanyaan: (1) Apa peran kedamangan dalam menyelesaikan perkara pidana adat? dan (2) Bagaimana kedudukan putusan adat sebagai pertimbangan hakim dalam memutus perkara pidana. Penelitian ini menggunakan metode hukum normatif dengan pendekatan perundang-undangan. Hasil penelitian menunjukkan bahwa hukum positif dan hukum adat yang berlaku dalam masyarakat mengatur penyelesaian perkara pidana melalui kedamangan, serta putusan adat berperan penting dalam pertimbangan hakim dalam perkara pidana di pengadilan.